THE INTERACTION EFFECT OF GLOBALIZATION AND HUMAN CAPITAL ON ECONOMIC GROWTH: THE CASE OF TURKEY (Third Sector Social Economic Review, 2020)
This study investigates the interaction effect of globalization and human capital on economic growth in Turkey. The autoregressive distributed lag (ARDL) bounds testing approach is applied in the study, and the dataset covers the period 1984-2017. The results show that the impact of globalization on economic growth is conditional on the human capital level in Turkey. The positive effect of globalization on economic growth increases as the level of human capital increases. That is to say, there is a strong complementary relationship between globalization and human capital in terms of enhancing the economic growth in Turkey.
Keywords: Economic Growth; Globalization; Human Capital; Interaction Effect.